The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10512-009-9144-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and investigation of a pulsed x-ray generator

Abstract: Portable and transportable instrumentation complexes based on pulsed x-ray generators with more stringent requirements for the spatio-temporal structure of the radiation field are needed for effective fast analysis of the state of the components of main pipelines. Specifically, aside from having small dimensions (maximum linear size ≤0.5 m), the radiation source must provide at distance 0.5 m from the target an exposure dose rate of at least ~0.1 mSv/sec with minimal area of the emitting surface of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Lowering the mAs level to reduce the patient radiation dose can easily be done on existing commercial CT scanners, while the other method proposed in our paper, namely reducing the number of projections to reduce the dose, is not straightforward on currently available commercial CT scanners due to the use of continuous x-ray generation mode. However, technically it is possible to modify the scanners to operate in high-frequency pulsed mode (Kang et al 2010, Myagkov et al 2009, Yue et al 2002 if there is a clinical need (such as the one suggested in this paper).…”
Section: Discussionmentioning
confidence: 99%
“…Lowering the mAs level to reduce the patient radiation dose can easily be done on existing commercial CT scanners, while the other method proposed in our paper, namely reducing the number of projections to reduce the dose, is not straightforward on currently available commercial CT scanners due to the use of continuous x-ray generation mode. However, technically it is possible to modify the scanners to operate in high-frequency pulsed mode (Kang et al 2010, Myagkov et al 2009, Yue et al 2002 if there is a clinical need (such as the one suggested in this paper).…”
Section: Discussionmentioning
confidence: 99%
“…Our idea of the TNLM function is inspired by the so called Non-local Means (NLM) method 16 originated in image processing † Decreasing the number of projections is not straightforward on currently available commercial CT scanners due to the use of continuous x-ray generation mode. However, technically it is possible to modify the scanners to operate in high-frequency pulsed mode [13][14][15] , if there is a clinical need (such as the one suggested in this paper).…”
Section: Introductionmentioning
confidence: 99%